The Role of Communication in Interorganizational Collaboration: The Case of Increasing Digital Inclusion in Public Libraries - Kulikauskienė, Kristina; Macienė, Jurgita (Information & Media, 2025)
Increasing digital inclusion in a general sense can be considered a complex problem that requires input from various parties interested in solving this problem, such as public sector organizations, among which, public libraries are particularly important, along with businesses, NGOs, and the public and its individual members. Interorganizational collaboration in increasing digital inclusion involves collaboration between organizations active in this field in initiating and implementing various activities aimed at increasing digital inclusion. In the process of interorganizational collaboration, various factors are identified that may influence the success of collaboration at different stages: the goals, vision, and values that unite the collaborating organizations, the ability to respond to change, effective management, trust, reciprocity, leadership, etc. Communication is one of the relational management mechanisms associated with open, frequent communication, the establishment of informal relationships and communication links between partners, and the consolidation of agreements, which shows the links between communication and all other factors that influence interorganizational collaboration.
Keywords: communication; interorganizational collaboration; digital inclusion; public libraries